COVID-19 and Corporate Finance. Issue 4 (13th August 2022) - Pagano, Marco; Zechner, Josef
Abstract: We distill evidence about the effects of COVID-19 on companies. Stock price reactions to the shock differed greatly across firms, depending on their resilience to social distancing, financial flexibility, and corporate culture. The same characteristics affected the response of firms' sales, employment, and asset growth. Despite the shock, firms expanded their balance sheets and liquidity by raising funds from banks, bonds, and equity markets. While listed firms reduced their leverage, unlisted ones, especially small and medium enterprises, increased it. Government support programs helped firms access external funding. We conclude by identifying unexplored research issues regarding the long-run effects of COVID-19 on companies. ( JEL : G11, G12, G13, G21, G24, G28, G32, G33, G35, G38, H81, H84)